Utilization Of Digital Media in Improving Student Literacy (Case Study at SDN 10 Rantau Selatan) - Ritonga, Aulia Rahma; Dalimunthe, Maulana Andinata; Nur'aini; Januarini, Erna (CONTENT: Journal of Communication Studies, 2024)
This study aims to see how to optimize the use of digital media in improving student literacy at SDN 10 Rantau Selatan. The research method used is qualitative with a case study approach. The data collection technique used is interviews and observations on four research informants, consisting of three students and one teacher. Data processing is carried out in three ways, namely Data reduction, Data presentation, and Drawing conclusions. The results of the study show that the use of digital media in improving student literacy is seen through more interactive and dynamic learning, by increasing reading interest and literacy skills. In addition, digital media is used to access broader and more diverse information, so that students can explore various topics and subject matter that support their intellectual development as a whole. The benefits of digital media are not only limited to improving students' literacy skills, but also strengthening the role of teachers as learning facilitators. By utilizing digital media, teachers can create a more inclusive and adaptive learning environment, where learning materials can be adjusted to the needs and abilities of each student.